The Emerald guide to Max Weber - Scott, John (Emerald guides to social thought, 2019)
This primer is the first introductory guide to the work of Max Weber designed specifically for students and those new to his work, providing a readable, clear, comprehensive and authoritative overview. The book discusses Weber's personal biography, placing him in the context of the development of the social sciences, covering his methodology as well as his work on religion, politics, economic history, music, and the development of capitalism. All that the reader needs to gain a good grasp of Weber's importance is contained in this book, which provides a firm foundation for the independent reading of Weber himself and for pursuing the many discussions and interpretations of his ideas. The book will appeal to readers in sociology, politics, history, law, religion, and other areas of the social sciences to which Weber made a contribution. The book includes a complete list of the best translations of Weber's works into English, an extensive guide to further reading highlighting uses and applications of Weber's ideas, and a brief overview of the German editions of his collected works.